Dynamometric analysis of the maximum force applied in aquatic human gait at 1.3 m of immersion - Roesler H.* (2006)
Background: This work had the objective to analyze the values of the vertical and anteroposterior components of the ground reaction force (GRF) during the aquatic gait and the influence of the speed and the upper limb position on the GRF components values. Methods: Sixty subjects, with average height between 1.6 and 1.85 m and average age of 23 years, were divided in three groups according to the immersion level. The citizens walked over a walking platform, which had two force plates attached. The platform was located at a depth of 1.3 m. The subjects walked over the platform in four different situations, with speed and upper limb position variations. For data analysis, descriptive and inferential statistics were used. Findings: For the vertical component, the force values varied between 20% and 40% of the subjects' body weight according to the different data collection situations. For the anteroposterior component, the force values reached between 8% and 20% of the subjects' body weight corporal, also according with the data collection situation. Interpretation (discussion): It was noted that for a given immersion level, the forces can vary according to the request that is imposed to the aquatic gait. It was concluded that either the speed as well as the position of the upper limb influence the values of the GRF components. An increase in the gait speed causes increase of the anteroposterior component (Fx), while an increase in the corporal mass out of the water causes increase mainly of the vertical component (Fy). Knowing the value of these alterations is important for the professional who prescribes activities in aquatic environment. © 2005 Elsevier B.V. All rights reserved.